Taxonomy of Aphelinoidea (Hymenoptera: Trichogrammatidae) species attacking eggs of the beet leafhopper, Circulifer tenellus (Hemiptera: Cicadellidae), in California - Walker, Gregory P.; Bayoun, Imad M.; Triapitsyn, Serguei V.; Honda, Jeffrey Y. (Zootaxa, 2005)
Species of Aphelinoidea Girault known to parasitize eggs of the beet leafhopper, Circulifer tenellus (Baker), in California were studied using both morphological and molecular characters. These include two introduced species (from Iran and Turkmenistan) as well as two indigenous species, A. zarehi n. sp. and A. roja n. sp. Earlier studies had identified the indigenous Aphelinoidea in California and other arid western states as A. plutella Girault, but we did not find putative A. plutella in our surveys of parasitoids of beet leafhopper eggs in California. We conclude that the earlier studies misidentified other indigenous species as A. plutella, and that at least some of these misidentifications were actually A. zarehi, one of the two new species described herein. A key to Aphelinoidea species known to parasitize beet leafhopper eggs in California is given. The key also includes A. plutella whose hosts are not known and for which we have no evidence as occurring in the western United States. DNA sequences support the separation of the four Aphelinoidea species reared from beet leafhopper eggs in California. Cross-mating tests also failed to show interbreeding between the taxa. Data are presented on developmental times of the two introduced species of Aphelinoidea.